Mitochondrial deficiency: a double-edged sword for aging and neurodegeneration - Bano, Daniele; Troulinaki, Kostoula (Frontiers in Genetics, 2012)
For decades, ageing was considered the inevitable result of the accumulation of damaged macromolecules due to environmental factors and intrinsic processes. Our current knowledge clearly supports that ageing is a complex biological process influenced by multiple evolutionary conserved molecular pathways. With the advanced age, loss of cellular homeostasis severely affects the structure and function of various tissues, especially those highly sensitive to stressful conditions like the central nervous system. In this regard, the age-related regression of neural circuits and the consequent poor neuronal plasticity have been associated with metabolic dysfunctions, in which the decline of mitochondrial activity significantly contributes. Interestingly, while mitochondrial lesions promote the onset of degenerative disorders, mild mitochondrial manipulations delay some of the age-related phenotypes and, more importantly, increase the lifespan of organisms ranging from invertebrates to mammals. Here, we survey the insulin/IGF-1 and the TOR signaling pathways and review how these two important longevity determinants regulate mitochondrial activity. Furthermore, we discuss the contribution of slight mitochondrial dysfunction in the engagement of pro-longevity processes and the opposite role of strong mitochondrial dysfunction in neurodegeneration.